2007
DOI: 10.1063/1.2777162
|View full text |Cite
|
Sign up to set email alerts
|

3 ω method to measure thermal properties of electrically conducting small-volume liquid

Abstract: This work presents a method to measure the thermal conductivity and heat capacity of electrically conducting small-volume liquid samples using the 3omega technique. A mathematical model of heat transfer is derived to determine the thermal properties from the 3omega signal considering the device geometry. In order to validate the model, an experimental apparatus has been designed and set up to measure the thermal properties (thermal conductivity and heat capacity) of seven different liquid samples. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
45
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 16 publications
(14 reference statements)
0
45
0
Order By: Relevance
“…Amongst non-steady state techniques for fluid property measurement, THW dominates. 4,8,20 THW analyzes the thermal impulse signal in the time domain, rather than in the frequency domain. THW sends a thermal impulse from a thin heating wire into the surrounding fluid of interest.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Amongst non-steady state techniques for fluid property measurement, THW dominates. 4,8,20 THW analyzes the thermal impulse signal in the time domain, rather than in the frequency domain. THW sends a thermal impulse from a thin heating wire into the surrounding fluid of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a significant part of the 3ω signal comes from the substrate, rather than the fluid under test, which decreases the signal of interest's size. 4 Solid-wire 3ω uses a solid heating wire that is immersed within the sample, rather than a microfabricated heater on a planar substrate. Similar to the standard 3ω, much of the periodic heating propagates radially into the high thermal effusivity metal wire, rather than into surrounding fluid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of this method to thermal analysis of small-volume liquid samples has demonstrated that the method is particularly suited for measuring k of samples which are electrically conducting or as small as subnanoliter in volume. [22][23][24] The sensor was inserted into a copper block inside a test chamber (Fig. 1(b)).…”
mentioning
confidence: 99%
“…A water bath was used to control the T of the chamber to within 60.1 C. The experimental setup is similar to those used for measuring k of small-volume liquid samples and solid thin films. [22][23][24][25] All measurements were repeated 10 times for each sample to assess the random error. The accuracy of measurement was tested by measuring DI water, ethylene glycol, and methanol; the deviations from reference values 26 were all <3%.…”
mentioning
confidence: 99%